2023
DOI: 10.3390/cancers15092640
|View full text |Cite
|
Sign up to set email alerts
|

The Cross Talk between Cellular Senescence and Melanoma: From Molecular Pathogenesis to Target Therapies

Abstract: Melanoma is a malignant skin tumor that originates from melanocytes. The pathogenesis of melanoma involves a complex interaction that occurs between environmental factors, ultraviolet (UV)-light damage, and genetic alterations. UV light is the primary driver of the skin aging process and development of melanoma, which can induce reactive oxygen species (ROS) production and the presence of DNA damage in the cells, and results in cell senescence. As cellular senescence plays an important role in the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…In various tumour types including malignant melanoma, necroptotic mediators are strongly suppressed, indicating acquired necroptotic resistance of tumour cells [153]. In line with this, senescent melanocytes that are capable of resisting cell death, are emerging as a potential cell-of-origin in melanoma and specific targeting of factors released by senescent melanocytes are showing promise in counteracting melanoma [154,155]. In keratinocyte-derived tumours, such as head and neck SCC, a substantial amount of necroptosis has been reported and high levels of phosphorylated MLKL were shown to correlate with lymph node metastasis and tumour progression [156].…”
Section: Cell Death and Skin Tumour Formationmentioning
confidence: 89%
“…In various tumour types including malignant melanoma, necroptotic mediators are strongly suppressed, indicating acquired necroptotic resistance of tumour cells [153]. In line with this, senescent melanocytes that are capable of resisting cell death, are emerging as a potential cell-of-origin in melanoma and specific targeting of factors released by senescent melanocytes are showing promise in counteracting melanoma [154,155]. In keratinocyte-derived tumours, such as head and neck SCC, a substantial amount of necroptosis has been reported and high levels of phosphorylated MLKL were shown to correlate with lymph node metastasis and tumour progression [156].…”
Section: Cell Death and Skin Tumour Formationmentioning
confidence: 89%
“…Like the CRGs discussed above, signaling pathways such as Cellular senescence and NF-kappa B signaling pathway are important mechanisms in melanoma. For example, studies have shown that the continuous accumulation of senescent melanocytes, fibroblasts, keratinocytes and immune cells in skin can promote melanoma pathogenesis and affect treatment, which is related to immune system aging [23]. Senescence inhibition therapy reduced tumor volumes and extended survival in a mouse melanoma model [23].…”
Section: Discussionmentioning
confidence: 99%
“…Increased lung cancerogenesis [203] More and more evidence points to the involvement of oxidative stress, which is brought on by high amounts of ROS, such as superoxide anions and hydrogen peroxide, in the development of melanoma [216,217]. When compared with nearby tissues or melanocytes, melanoma cells produce a lot of ROS, which they then excrete into extracellular space [218].…”
Section: Humansmentioning
confidence: 99%